MAKNA LAGU DOLANAN ILIR-ILIR - Rabimin Rabimin (Institut Seni Indonesia Surakarta, 2009)
The traditional childrenâ€™s song entitled Ilir-ilir is predicted to come into existence in the 15th century. It is written in many manuscripts that the composer of this song was Sunan Giri. The song known well up to now has undergone various developments in lyrics, meaning, function and garap. In case of the function, the song which was only sung by children in the past, has developed into, amongst other things, a means of midodareni ritual of Javanese wedding, entertainment, Islamic proselytism, dance accompaniment, consciousness recovery, war motivation, education and so on. In case of garap development, the song which was sung without instrumental accompaniment has developed in various ways, that is, (1) the song is accompanied by gamelan agung rebana and lesung; (2) it is presented as an instrumental song; (3) it is arranged in the form of lancaran, srepeg, ketawang, ladrang; (4) it is arranged in lancar (fast), tanggung (medium-fast), dados (slow), wiled, rangkep rhythmes; (5) it is arranged in slendro and pelog (pentatonic) and even diatonic pitch; (6) it is arranged in patet nem, lima, manyura, and sanga; (7) the lyric which was at first only one pada (couplet) has become three couplets; (8) the lyric has a variety of differences due to needs, situation, the influence of local culture, and the attitude of creative artists. Key words :Â ilir-ilir, traditional childrenâ€™s song, development